The Effectiveness of E-Modules Based on Problem-Based Learning toward Student Learning Outcomes in Educational Profession Courses - Vidianti, Ade; Adesti, Anita; Pebriantika, Leni (Teknodika, 2024)
The purpose of this study is to develop an E-Module based on problem-based learning and train students to solve problems critically and scientifically in professional education courses. The research method that will be used is research and development. The development model applied is the one proposed by Rowntree which consists of three stages: planning stage, development stage and evaluation stage. The planning stage is carried out with the following activities: a) Needs analysis; b) Formulating general and specific objectives; c) Compiling an outline of the contents; d) Determining concept analysis; e) Determining media and equipment. At the product development stage, it will be carried out using software. However, Rowntree's model is not complete in the product evaluation section, therefore this model will be collaborated with Tessmer's evaluation model so that the incompleteness of Rowntree's model will be covered by the advantages of Tessmer's formative evaluation model. The data collection techniquein this study used questionnaires and learning outcome tests. Tessmer's model has five stages of evaluation, namely self-evaluation, expert reviews; one-to-one, small group, and field test, the results will be assessed using a questionnaire. The more often a product is evaluated, the better the results will be, with the collaboration of these two models, it is expected to produce a valid, practical, and effective module. The quality and effectiveness of E-Modules based on problem based learning are obtained from the pretest and posttest results with an N-gain of 0.76 in the high category. From these results, it shows that the implementation of E-Modules based on problem based learning in the class has increased learning outcomes in the high category, so it can be concluded that e-modules based on problem based learning are effective to be applied to educational profession courses